Levantamiento topográfico de una aldea precolombina (900-1550 a.C.) - Lara Morales, Gustavo Manuel (2018)
The authors discuss methodological aspects of the topographic and archaeological analyses being carried out in Barranca, a pre-Columbian settlement in San Ramón, Alajuela. A discussion is also presented on the relevance of geographic analysis for archaeological interpretations. The work is the result of an interdisciplinary collaboration between professionals in archaeology and topographic engineering. The article describes the technical aspects of field work and analysis of archaeological and spatial information to reconstruct ancient socio-cultural dynamics.